Pengaruh Small Group Discussion terhadap Hasil Belajar Peserta Didik Kelas VIII pada Mata Pelajaran IPA SMP di Jawa Timur - Nadilatus Salsabila; Mayla Syifani Zulfa; Nanda Zakiatus Solihah; Firdha Yusmar; I Ketut Mahardika; Rizka Elan Fadilah (Pendidikan Fisika FKIP UNEJ, 2022)
This article aims to determine the effects of small group discussion on science subjects on student’s learning outcomes. The type of method use in writing scientific articles is literature study. This research was conducted on eight grade students of junior high school in East Java. To improve student achievement, it is necessary to carry out a learning activity using learning methods, one of wich is the Small Group Discussion Method. This research was carried out through this literature study on VIII Junior High School students. The method of data collection in this research is through literature study. The data analysis method is descriptive. The results obtained from this study are the Small Group Discussion Method can improve student learning achievement. These results after ananalysis using a description of the analys conclude that the use of the Small Group Discussion Method can improve creativity and science learning achievements of class VIII students.